2016
DOI: 10.1037/ccp0000132
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a very brief, multicomponent web-based alcohol intervention for undergraduates with a focus on protective behavioral strategies.

Abstract: Objective THRIVE (Kypri et al., 2009; 2013; 2014), a very brief, freely-available, multi-component web-based alcohol intervention originally developed and tested among students in Australia and New Zealand, was tested in the United States. We also evaluated effects of systematically varying the protective behavioral strategies (PBS) component of the intervention to include shorter, focused lists of Direct (e.g., alternating alcoholic with non-alcoholic drinks) or Indirect (e.g., looking out for friends) strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…There were no significant reductions in drinking consequences for any of the treatment groups compared to MA, though the TA group’s consequence reductions trended towards significance. This is similar to the findings of previous studies on brief in-person and web-based interventions which revealed few meaningful reductions in alcohol consequences [ 27 , 35 , 36 ]. It is possible that the reductions in drinking quantity or frequency did not translate into significant reductions in consequences.…”
Section: Discussionsupporting
confidence: 91%
“…There were no significant reductions in drinking consequences for any of the treatment groups compared to MA, though the TA group’s consequence reductions trended towards significance. This is similar to the findings of previous studies on brief in-person and web-based interventions which revealed few meaningful reductions in alcohol consequences [ 27 , 35 , 36 ]. It is possible that the reductions in drinking quantity or frequency did not translate into significant reductions in consequences.…”
Section: Discussionsupporting
confidence: 91%
“…PFI participants experienced slightly, although not significantly, stronger declines from baseline to 1 month and both groups decreased alcohol-related problems over the 9 months. The lack of a commensurate impact on problems in light of observed immediate decreases in drinking may seem a bit surprising; however, this is in line with other studies of brief alcohol interventions showing null results on problems (e.g., Leeman et al, 2016) or differential impact on problems versus use (e.g., Borsari et al, 2012). It is also consistent with research showing brief alcohol intervention’s impact on problems to be relatively weaker in magnitude than consumption (Tanner-Smith et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The combination of CBT and motivational interviewing became increasingly common following the Combined Behavioral Intervention (CBI) approach (Combine Study Research Group, ) employed for AUD in the COMBINE Study (Anton et al., ). Other programs included in this meta‐analysis are “packaged” approaches that combine cognitive‐behavioral relapse prevention skills with personalized feedback, such as the Tertiary Health Research Intervention via Email ( THRIVE ; Leeman et al., ), or with acceptance and mindfulness exercises ( Balance ; Brendryen et al., ). Thus, the number of “pure” CBT technology‐based interventions, and therefore the evidence for their efficacy, is currently relatively limited.…”
Section: Discussionmentioning
confidence: 99%